Analisis Kesalahan Penyelesaian Soal Aljabar pada Mahasiswa Program Studi Pendidikan Matematika STKIP Singkawang - Rosmaiyadi (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2018)
In the educational world, the challenge of some universities is to create graduates who are competent in their field. One of the competencies required of graduates of Mathematics Education in STKIP Singkawang is skills in solving math problems correctly and appropriately. According to reality on the ground, there are many students turned out to have any errors in problem-solving algebra. This is because the material Algebra is one area of Mathematics, that is considered difficult. The purpose of this study is to describe and identify errors Algebra students work on the problems and the factors that affect the mistakes made. The results obtained student errors relating to the algebraic concepts of 17.5%, the error associated with the error count of 25.9%, an error in the algorithm deviation of 8.76%, a typing error and the use of the mark by 5.13%, to answer any error of 1.7%, a matter which was not finished at 21.2% and answer questions that are not answered at all by 10.3%. Internal factors affecting the students make mistakes in solving algebra include the physical and psychological factors, but external factors include family and community environment factors.